Desain Dan Pembuatan Alat Destilasi Asap Cair (Liquid Smoke) - Abbas, Said Hi; Tjiroso, Bambang (Department of Electrical Engineering, University of Patria Artha, 2021)
Liquid smoke is a condensate liquid from the pyrolysis of coconut shells which contains the main constituent compounds of acids, phenols, and carbonyls, so it is widely applied as a natural preservative in food and provides sensory characteristics in the form of aroma, colour, and a distinctive taste in food products and as an anti-bacterial. The research objective was to design, manufacture, and test the liquid smoke distillation apparatus. The method used in this research is an experimental method where the activities carried out include designing, making, and testing. The result is that the furnace is made based on the results of the initial design with a height of 61 cm, width 41 cm and length 41 cm. The top of the furnace is conical with a cone height of 34 cm. The condenser tube is rectangular in shape with a width of 40.5 cm, length 40.5 cm and a height of 60.5 cm. the condenser tube serves to accommodate water which is used as a cooling medium. The inside of the condenser tube contains ¾ inch pipe which is formed into a rectangular spiral into 5 stacks. The pipe functions to flow the smoke from the combustion products from the gas phase into a liquid by cooling it with water as a medium. the manufacture of the liquid smoke distillation device has been carried out by the design, but there are some minor changes in the process of making the distillation device. Tests are carried out using raw materials, namely coconut shells and coconut fibers as fuel. Tests carried out with variations in the time and volume of liquid smoke generated from the distillation device. The test results from the liquid smoke distillation tool obtained 400 ml of liquid smoke from the distillation in 2 hours